Optimization of a comprehensive rehabilitation program for patients with motor dysfunction following a stroke - Sharafova Inobat Axmedjonovna,; Saydaliyeva Sevara Shavkat qizi, (American Journal Of Biomedical Science & Pharmaceutical Innovation, 2025)
This study aims to optimize rehabilitation strategies for stroke patients with motor dysfunction by integrating traditional therapies with emerging technologies. A mixed-methods approach will be used to evaluate the effectiveness of a personalized rehabilitation program that combines physical therapy, occupational therapy, robotic-assisted therapy, virtual reality (VR), and neurostimulation. Participants will include stroke patients with motor impairments, and outcomes will be measured in terms of motor recovery, functional independence, and quality of life. Data will be analyzed through both quantitative (e.g., Fugl-Meyer Assessment, Stroke Impact Scale) and qualitative methods (e.g., interviews, thematic analysis). The study emphasizes the importance of patient-centered care and evidence-based practices, with the goal of providing more effective and individualized rehabilitation for stroke survivors.